The Genesis of Greek Philosophico-Scientific Thought n Light of World System Theory - Muhammad Dom, Adi Setia (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
The Genesis of Greek Philosophico-Scientific Thought n Light of World System Theory